Legal Issues Pertaining to High Altitude Platform Station Implementation in Indonesia as an Archipelagic State - Yaries Mahardika Putro; Ridha Aditya Nugraha; Taufik Rachmat Nugraha; Rio Christiawan; Aldhanti Bodhihanna; Jason Pratama Ong; Muhammad Revaldi Testarosa (Udayana Journal of Law and Culture, 2023)
Information is a necessity for the interests of government, the economy, social culture, as well as defense and security in the era of industrial revolution 4.0. Since 1976, the Indonesian government has been working on developing a satellite communication system starting with the Palapa A1 Satellite, followed by its subsequent generations. However, this system has limitations, particularly in providing coverage to rural areas in Indonesia. To address this issue, the government has started the procurement of the Wahana Dirgantara Super or High-Altitude Platform Station (HAPS) in Indonesia. HAPS are stations positioned at altitudes of 20 to 50 km above the Earth's surface. Given Indonesia's geographical location, HAPS is seen as the most suitable solution as it utilizes non-ground terrestrial technology to improve information and communication technology coverage in rural areas. However, the location on which the HAPS is positioned might trigger new issues, particularly with regard to state sovereignty and disruption of flight traffic. The operation of HAPS also needs further consideration so that the protection of personal data in Indonesia will not be disrupted. This article employs normative juridical research as a methodology. The research collected and analyzed primary sources in the form of law, regulation, and policy at the national and regional levels, as well as secondary sources that are available in textbooks, journal articles, and website content. This article aims to explain the development of HAPS regulations based on international law and national law and to examine the legal issues related to the procurement of HAPS in Indonesia . At the end, this article suggests that it is necessary to regulate HAPS in Indonesia with reference to aviation safety, security, and liability issues as well as maintaining state sovereignty and ensuring personal data protection.